In Vitro Assay of Lytic Bacteriophage to Suppress the Growth of Ralstonia syzygii subsp. indonesiensis, the Causal Pathogen of Potato Wilt Disease - Azizah, Nur; Irda Safni (Talenta Publisher, 2024)
Bacterial wilt disease, the one of the major diseases of potatoes, caused by Ralstonia syzygii subsp. indonesiensis (Rsi). Many efforts have been made to control bacterial wilt disease, including physical control, chemicals, and the use of bacteriophages. Previous studies have shown that bacteriophage application in controlling plant diseases is a fast-expanding area and has great potential to replace chemical methods. This study aims to determine the potential of lytic bacteriophage in suppressing the growth of Rsi in vitro. This study used a Non-Factorial, Completely Randomized Design with 3 replications and 6 treatment levels: R1 (Rsi isolate 1 without bacteriophage), R2 (Rsi isolate 1 with bacteriophage), R3 (Rsi isolate 2 without bacteriophage), R4 (Rsi isolate 2 with bacteriophage), R5 (Rsi isolate 3 without bacteriophage), and R6 (Rsi isolate 3 with bacteriophage). The results showed that bacteriophage could reduce the Rsi population at 24 hours by looking at the optical density (OD) value of 600 nm wavelength and growing on NA medium using the spread-plate method. The best treatment was at R6 with a population of 1 x 108cfu/ml Rsi. This research suggests that bacteriophage has the potential to suppress the growth of Rsi, which causes potato bacterial wilt disease, in vitro.